Social Networks and the Image Projected by European Royal Families. - López-Marcos, Casandra; Vicente-Fernández, Pilar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In Europe, ten states are conventional monarchies, whose royal families constitute an icon of national unity as well as a legacy of historical traditions, highlighting their role as representatives of their countries. This research studies the image projected by European royal houses through digital platforms. The objective is to determine what graphic resources, visuals, and descriptions they use in the biography section on their Facebook, X, and Instagram accounts. The results of the content analysis show a tendency to use resources of an institutional nature, in addition to the prominence of symbolic components as coats of arms, flags and national heritage.